Positive Discipline in Managing the Classroom at STIKIP PGRI West Sumatera - Hevriani Sevrika (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2017)
This study was descriptive design because the writer only wanted to describe about the discipline that was used by the lecturer in the classroom. The numbers of lecturers who were as the sample of this study were two English lecturers who were teaching Grammar II subject at STKIP PGRI WEST SUMATERA. Padang, so the writer took them all as the sample through total sampling technique. To find the data in this study, the writer used some instruments which are observation checklist, video and field note. The process in taking the data which was started from coming into the classroom observed the lecturer. The writer recorded the lecturer in two meetings for each lecturer. Then writer checked the data by using observation checklist and field note.  Thus, the result of this study was all of lecturers used positive discipline in managing the classroom. Those, the lecturers used thirteen types activities of positive discipline which can be classified as following: the first type was showing a positive attitude. The lecturers show a positive attitude which was applied by two English lecturers. There were lecturer A, and B. Second, the lecturers show interest. The lecturer show interest was applied by all of the lecturers. Third, the lecturer focused on positive thinking. Fourth, the lecturer used supportive tone of voice. Fifth, they showed a sense of humour. Sixth, they listened to the students talk and taking them seriously. Seventh, acting tough the students enjoy with their jobs, it was used by all the lecturers. Eighth, used appropriate body language; it was applied by all of the lecturers. Ninth, they lowered body position. Tenth, the lecturers listened their students before judging. Eleventh, the lecturers were consistent in giving punishment and rules. Twelfth, the lecturer A separated the behaviour from the students. Thirteenth, respect diversity was applied by all the lecturers